The Value of Knowledge The Economics of Enterprise Knowledge and Intelligence - Powell, Timothy W. (Knowledge services, 2020)
Knowledge is an economic asset of great importance and value to the modern organization; however, it is too often not managed carefully as such. This book presents practical frameworks and methods for the knowledge professional -- and his/her organization -- to identify, actualize, and maximize the economic value of knowledge.